Enhancement of Adjuvant Functions of Natural Killer T Cells Using Nanovector Delivery Systems: Application in Anticancer Immune Therapy - Ghinnagow, Reem; Cruz, Luis Javier; Macho-Fernandez, Elodie; Faveeuw, Christelle; Trottein, François (Frontiers in Immunology, 2017)
Type I Natural Killer T (NKT) cells have gained considerable interest in anticancer immune therapy over the last decade. This “innate-like” T lymphocyte subset has the unique ability to recognize foreign and self-derived glycolipid antigens in association with the CD1d molecule expressed by antigen presenting cells. An important property of these cells is to bridge innate and acquired immune responses. The adjuvant function of NKT cells might be exploited in the clinics. In this review, we discuss the approaches currently being used to target NKT cells for cancer therapy. In particular, we highlight ongoing strategies utilizing NKT cell-based nanovaccines to optimize immune therapy.